(untitled) (Revista Contexto & Saúde, 2026)
The COVID-19 pandemic caused changes in the population’s lifestyle and contributed to increased exposure to stress, especially among mothers. However, there are few studies that have investigated the impact of the pandemic on stress, eating behavior, and lifestyle of this population. The present study aimed to analyze the relationships between perceived stress levels, eating behaviors, and health-related lifestyle of Brazilian mothers during the COVID-19 pandemic. To this end, an online questionnaire was used, consisting of sociodemographic data, the Perceived Stress Scale (PSS-10), the Three-Factor Eating Questionnaire (TFEQ-R21), and changes in lifestyle habits during the COVID-19 pandemic. Participants’ perceived stress had a median of 24.0 (IQR: 19.00-29.00), with moderate and high levels in 92.8% (n=167) of participants. Higher levels of stress were positively related to Emotional Eating behaviors (r=0.379; p<0.001) and Loss of Control Eating (r=0.350; p<0.001). Moreover, higher stress levels were also associated with physical inactivity, poorer sleep quality, and increased consumption of alcohol, cookies, and sweets. It is concluded that the high level of stress perceived by Brazilian mothers during the COVID-19 pandemic is associated with dysfunctional aspects of eating behavior and negative changes in maternal lifestyle habits.